Regional Diversification of Expenditure Structure in Poland: a GCA Approach - Gostkowski, Michał; Jałowiecki, Piotr; Tekień, Agnieszka (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The paper presents the results of the analysis of household expenditure structures in Poland using Grade Correspondence Analysis (GCA). Studies have shown that in the analyzed period the structure of consumer expenditure changed. The share of food and non-alcoholic beverages expenditures decreased steadily, while the share of expenses related to maintenance and household equipment, culture and recreation, or restaurants and hotels steadily increased. Further studies have shown that the structure of consumer expenditures in Poland is diversified regionally. The greatest variation occurs between the north-eastern region voivodeships and the central region/south-west voivodeships.